Effectiveness Of Milk Supplementation On The Nutritional Status Of Undernourished Preschool Children - Koh, Chu Sing (1997)

(untitled)
The aim of the study is to determine the effectiveness of the milk supplementation in improving the nutritional status of undernourished preschool children. Three comparable experimental groups of undernourished preschool children (n=458), ages one to four years old, were selected. Children in the "1-kg group" were provided with one kg of milk powder per month for a period of nine months, while those in the "3-kg group" were given three kg of the supplement. At the start of the study, there was no significant difference in the anthropometric measurements, biochemical and haematological parameters, as well as the dietary intake of the children in the three groups. The three groups